We wait for the sun - Roundtree, Dovey Johnson, 1914-2018; McCabe, Katie (Roaring Brook Press, 2021)
The late Civil Rights attorney and activist shares a poignant moment from her childhood beside her wise grandmother, who taught Roundtree the values of self-worth, strength and justice that inspired the co-author's boundary-breaking career.